Antitubercular and immunomodulatory activities of Eugenia astringens n-hexane fraction - Igor Santiago-Carvalho; Thatiana Lopes Biá Ventura Simão; Sanderson Dias Calixto; Thalissa Cozentino de Albuquerque; Tatiana Ungaretti Paleo Konno; Rafael Moysés Salgado; Michelle Frazão Muzitano; Shaft Corrêa Pinto; Elena Lasunskaia (Elsevier, 2022)
Background: In Brazil, the Eugenia genus is traditionally used to treat several types of human diseases, including diabetes, gastric ulcers and rheumatoid arthritis. Previous studies demonstrated that medicinal properties of Eugenia astringens Cambess (Myrtaceae), popularly known as "baguaçu'' in Brazil, were associated with anti-inflammatory and antimicrobial activities exhibited by the plant extracts. Anti-tubercular effects of E. astringens have not been elucidated yet. Aim of the study: To study anti-tubercular and immunomodulatory potential of the E. astringens leaves extracts (syn. E. umbelliflora O. Berg), as well as the chemical profiles of active fractions. Methods: The plant material was collected in the Parque Nacional da Restinga de Jurubatiba (Rio de Janeiro) and the leaves were dried and extracted with ethanol. The extracts were partitioned, to yield n-hexane (Hex), dichloromethane (DCM), ethyl acetate (EtOAc) and n-butanol (BuOH) fractions. The crude extract and fractions were evaluated for antitubercular effects in broth cultures of M. tuberculosis strains and assessed for cytotoxicity in mammalian cell cultures by the MTT method. The Hex fraction, exhibiting low cytotoxicity and stronger inhibitory effect on mycobacterial growth relative to other fractions, was selected for the further studies. Immunomodulatory effects of the Hex fraction were evaluated in the RAW 264.7 macrophages, stimulated by LPS to produce inflammatory mediators, such as TNF-α, IL-6 and nitric oxide. Additionally, the effects on mitogen-stimulated human lymphocyte functions were estimated by measuring cell proliferation and IFN-γ production. Results: The E. astringens Hex fraction inhibited growth of mycobacterial strains both in the bacterial culture and infected macrophages, demonstrating strong anti-tubercular potential. In addition, this fraction suppressed secretion of inflammatory cytokines and reduced production of nitric oxide through inhibition of iNOS expression in the LPS-stimulated macrophages. In the mitogen-stimulated lymphocyte assay, Hex fraction inhibited cell proliferation but did not alter IFN-γ production. GC-MS analyses showed that the Hex fraction is composed by caryophyllene-type, eudesmane-type, cadinene-type, and aromadendrene-type sesquiterpenes; and 28 compounds were identified, including spathulenol, previously described for antitubercular acitivity. It is possible that the overall biological efficiency of the Hex fraction depends on the cumulative and/or synergistic effect of these sesquiterpenes. Conclusion: The Hex fraction of E. astringens leaves showed strong antitubercular and immunomodulatory activities, demonstrating pharmacological potential of the identified compounds for the development of new anti-TB drugs.